2006
DOI: 10.1001/archpsyc.63.10.1090
|View full text |Cite
|
Sign up to set email alerts
|

Smaller Neocortical Gray Matter and Larger Sulcal Cerebrospinal Fluid Volumes in Neuroleptic-Naive Women With Schizotypal Personality Disorder

Abstract: The smaller neocortical gray matter volume and larger sulcal CSF volume provide evidence of the brain basis of this personality disorder and emphasize the communality of brain abnormalities in the schizophrenia spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 77 publications
0
21
0
Order By: Relevance
“…First, several studies have demonstrated that structural or functional variability in these regions is critically associated with individual differences in cognitive and affective processing and personality traits . Second, functional or structural alterations in the same regions have also been found associated with borderline personality disorder ; antisocial personality disorder ; and schizotypal personality disorder . Therefore, consistently with our findings, alterations in these regions seem to underlie both non‐pathological and pathological personality traits, although the nature of the difference between the two (i.e., qualitative vs. quantitative) is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…First, several studies have demonstrated that structural or functional variability in these regions is critically associated with individual differences in cognitive and affective processing and personality traits . Second, functional or structural alterations in the same regions have also been found associated with borderline personality disorder ; antisocial personality disorder ; and schizotypal personality disorder . Therefore, consistently with our findings, alterations in these regions seem to underlie both non‐pathological and pathological personality traits, although the nature of the difference between the two (i.e., qualitative vs. quantitative) is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…4 Recent magnetic resonance imaging (MRI) studies have provided evidence of MRI brain similarities between SPD and schizophrenia (see articles on schizophrenia by McCarley et al 5 and Shenton et al 6 ). Schizotypal personality disorder MRI abnormalities compared with healthy control (HC) subjects include both global 7,8 and regional volume reductions in gray matter of the neocortex ( Table 1). Reports of regional gray matter volume (GMV) reductions in SPD include (1) temporal lobe superior temporal gyrus (STG), 9,17,21,26,30,31 Heschl gyrus within the STG, 10 middle temporal gyrus, 8,29 fusiform gyrus, 27 and hippocampus 16,24 ; (2) frontal lobe superior and inferior frontal gyri, 8,21 insula, 20,21 and cingulate gyrus 29,30 ; (3) parietal lobe 8,28 ; and (4) basal ganglia.…”
Section: Conclusion and Relevancementioning
confidence: 99%
“…The procedure for isolating neocortex is described elsewhere (46). Briefly, neocortical ROI delineation included all six-layered neocortex and excluded the major portion of nonneocortical cortex, including limbic cortical areas (with the exception of the pyriform cortex) and most of paralimbic cortex, with the exception of portions of cingulate, insula, and temporal pole (for anatomic description: ref.…”
Section: Region-of-interest Definitionsmentioning
confidence: 99%